History of Muslim Minorities in Myanmar Revisited - Hidayat, Asep Achmad; Nurcahya, Yan; Sugiarto, Deri; Hambaliana, Dandie; Suwanda, Satya Adilaga; Oksa Putra, M Zikril (Jurnal Iman dan Spiritualitas, 2025)
This research aims to analyze the historical development of Islam as a minority religion in Myanmar, focusing on the role of the Muslim community, which has existed since the 9th century through maritime trade routes. The method employed is a literature study by collecting relevant books and academic writings. The research follows four steps: heuristics, source criticism, interpretation, and historiography. The findings reveal that Islam was introduced to Myanmar by Arab, Persian, and Bengali traders who settled in the Arakan coastal region (now Rakhine State). The Muslim community comprises various ethnic groups, including Bamar, Kamein, Panthay, Malay, and Rohingya. The historical relationship between the Arakan Kingdom and the Bengal Sultanate in the 15th century significantly strengthened Islamic influence in the region and shaped the Rohingya identity as a community with deep cultural and historical roots. Although the Muslim population assimilated into local culture, they faced escalating challenges post-Myanmar’s independence in 1948 due to restrictive citizenship laws. The situation deteriorated with acts of violence in 2012 and 2017, leading to a humanitarian crisis as thousands of Rohingya sought refuge in Bangladesh. This research contributes a historical perspective on the social and political dynamics influencing Myanmar’s Muslim minority and highlights the complexities of the Rohingya crisis.